Pengaruh Corporate Governance terhadap Tax Avoidance pada Perusahaan Manufaktur yang Terdaftar di BEI Tahun 2021-2023 - Valen Miranda; Agrianti Komalasari (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
The study try to investigate how corporate governance practices affect tax avoidance in manufacturing companies (listed on IDX, 2021-2023). The five independent variables are foreign ownership, audit committee, audit quality, independent board of commissioners, and institutional ownership, which are analyzed to obtain findings on their influence on tax avoidance, proxied by the Effective Tax Rate (ETR). The findings of the study show tax avoidance is not significantly affected by these five independent variables, either individually or collectively. These findings indicate that tax avoidance in manufacturing companies is not directly affected by the corporate governance mechanisms measured through these variables. This research provides implications for regulators and companies in evaluating the effectiveness of implementing various principles of good corporate governance in the oversight of tax policies.